EFFECTS OF ABRASIVES DURING ACCELERATED SIMULATION OF MECHANICAL CORROSION OF CEMENT COMPOSITES USING ABRASIVE WATER FLOW - Petr Hlaváček; Libor Sitek; Dagmar Klichová; Lenka Bodnárová (Acta Polytechnica CTU Proceedings, 2019)
The paper deals with the use of the abrasive water flow technology in an accelerated simulation of the process of mechanical degradation of surface layers of cement-based composites by flowing liquids. Effects of the abrasive particle size and the mass flow rate of abrasives in an abrasive water flow impacting on the surface of concrete samples have been studied. In addition, suitability of the application of the abrasive water flow for the simulation of real situation of the surface wear by flowing liquids has been evaluated.